The Indigenous Idea of Gender Equality: Husband-Wife Relationship in the Manuscript of Adābul Mu’āsyarah - Sheila Fakhria; Moh. Sholeh Afyuddin; Muhammad Nazir Alias (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
Literacy in pesantren still places women as the second class, especially in the study of women's fiqh or husband-wife relations. This phenomenon has attracted researchers to conduct research on one of the books by Nusantara scholars used by Islamic boarding schools, whether it contains gender equality or not. This research focused on one of the books, Adābul Mu’āsyarah, which describes the ethics of husband and wife relations in fostering a harmonious family. By using a literature study with analytical techniques in the form of content analysis and a gender studies approach, this research found that the contents of this book by KH Yasin Asmuni have provided equal space in household relations between husband and wife. Although it cannot be denied that there are still many patriarchal terms, such as defining women as humans who lack reason and emotion, which makes men superior to women in several ways. This phenomenon of patriarchal understanding has been impacted by several factors, such as the author's background, patriarchal culture and the wave of studies that narrowed a unique case into a general provision. This research is expected to provide references and a new paradigm in describing equal husband-wife relations.